"… Trial and error …": Speech-language pathologists' perspectives of working with Indigenous Australian adults with acquired communication disorders. (2nd September 2016) - Cochrane, Frances Clare; Brown, Louise; Siyambalapitiya, Samantha; Plant, Christopher
Abstract: Purpose : This study explored speech-language pathologists' (SLPs) perspectives about factors that influence clinical management of Aboriginal and Torres Strait Islander adults with acquired communication disorders (e.g. aphasia, motor speech disorders). Method : Using a qualitative phenomenological approach, seven SLPs working in North Queensland, Australia with experience working with this population participated in semi-structured in-depth interviews. Qualitative content analysis was used to identify categories and overarching themes within the data. Result : Four categories, in relation to barriers and facilitators, were identified from participants' responses: (1) The Practice Context; (2) Working Together; (3) Client Factors; and (4) Speech-Language Pathologist Factors. Three overarching themes were also found to influence effective speech pathology services: (1) Aboriginal and Torres Strait Islander Cultural Practices; (2) Information and Communication; and (3) Time. Conclusion : This study identified many complex and inter-related factors which influenced SLPs' effective clinical management of this caseload. The findings suggest that SLPs should employ a flexible, holistic and collaborative approach in order to facilitate effective clinical management with Aboriginal and Torres Strait Islander people with acquired communication disorders.